Законодавчі аспекти оцінки відповідності засобів вимірювальної техніки - Кондратенко, В. О. (ХНУРЕ, 2024)
The purpose of the work is to reduce the risk of violation of the requirements of technical regulations and legislation of Ukraine on metrology and metrological activities during release from production and providing measuring equipment on the market. The existing contradictions in technical regulations are considered, which allow manufacturers of measuring equipment or their authorized representatives (including importers) to violate the requirements of technical regulations. Proposed to consider and recognize existing contradictions as a risk of violation of the requirements of the legislation of Ukraine on metrology and metrological activities, a method for minimizing these risks is proposed.
Keywords: вимірювальна техніка; оцінка відповідності